La otra piel : el segundo caso del sargento Aector McAvoy - Mark, David John, 1977-; Porras Sánchez, María; Mark, David John, 1977- (Madrid : Siruela, 2014)
Suspecting foul play in the alleged suicide of a depressed man in an East Yorkshire neighborhood where a new gang has recently seized control of the local drug trade, Detective Sergeant Aector McAvoy finds the investigation pitting him against elite political figures and other powerful individuals who murderously protect their secrets.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: McAvoy, Aector -- Fiction; Murder -- Investigation -- Fiction; Police -- England -- Fiction; Hull (England) -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Electronic books